Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1373/jalm.2017.023630
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability and Normal Ranges of Whole Blood and Plasma Thrombin Generation

Abstract: Background Assays measuring thrombin generation (TG) in plasma increasingly gained attention in the field of thrombosis and hemostasis. Adaptation of the method enabled the measurement of TG in whole blood (WB). Despite their potential, TG assays did not reach the stage of universal clinical application, partly because of the absence of normal ranges. Our study aimed to accurately determine normal ranges and interindividual variability of TG and correlate results with coagulation factor level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 36 publications
10
32
2
Order By: Relevance
“…In a recent study, we have shown that, in our laboratory, there is no significant difference in TG parameters between men and women who are not using oral contraceptives . Similarly, we did not observe correlations between TG parameters and age within our cohort .…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In a recent study, we have shown that, in our laboratory, there is no significant difference in TG parameters between men and women who are not using oral contraceptives . Similarly, we did not observe correlations between TG parameters and age within our cohort .…”
Section: Discussioncontrasting
confidence: 45%
“…31 Similarly, we did not observe correlations between TG parameters and age within our cohort. 31 This is not necessary a problem, because both platelet function and coagulation are not affected by age or gender. 30 Another study showed that there are no discordant effects of age on the relation between platelet function and HMB.…”
Section: Discussioncontrasting
confidence: 41%
“…To characterize changes in their hemostatic profile, we measured VWF (total antigen, 126 VWF propeptide, 62 and active VWF) levels, FVIII, 126,127 thrombin generation, 128 fibrinogen levels, 127 platelet activation, 129 and clot lysis time 127 (methods according to references). Peripheral blood cell counts in citrated whole blood were determined using a COULTER counter analyzer (Beckman Coulter, Woerden, the Netherlands).…”
Section: Appendix: Methodology For the Pilot Studymentioning
confidence: 99%
“…In this issue of The Journal of Applied Laboratory Medicine, Bloemen et al (12) describe development of reference intervals for TGA in whole blood, platelet-rich plasma, and platelet-poor plasma. As evidence of the lack of standardization for this assay, the authors report 9 different reference intervals that would need further separation based on sex and oral contraceptive use.…”
mentioning
confidence: 99%
“…For example, it was recently reported that predicting risk of bleeding in patients with factor XI deficiency required that a TGA be performed with platelet-rich plasma and corn trypsin inhibitor (12). This set of conditions proved superior to either PTT-based factor-XI-activity assays, notorious for not predicting bleeding in these patients, or standard plasma-based TGAs.…”
mentioning
confidence: 99%